Composite biologically active filter (BAF) with zeolite, granular activated carbon, and suspended biological carrier for treating algae-laden raw water. (August 2021) - Xiang, Shuo; Han, Yutong; Jiang, Chao; Li, Mengyan; Wei, Lecheng; Fu, Jiashen; Zhu, Liang
Abstract: In this study, a composite biologically active filter (BAF) packed with suspended biological carrier (SBC), zeolite, and granular activated carbon (GAC) in order, was set to pretreat the algae-laden synthetic raw water. Over the long-term operation, stable and effective treatment was achieved under the algae concentration as high as 16.64 × 10 8 cell/L, with average removal efficiencies of NH4 + -N, Total Organic Carbon (TOC), and algae cells of 97.7%, 64.0%, and 78.6%, respectively. The pollutant removal of each filter were quantitatively assessed. The results revealed zeolite mainly contributed to the adsorption of NH4 + -N (50.1%), GAC enriched the most functional microorganisms and contributed to nitrification (57.1%) and organics biodegradation (TOC: 63.9%, microcystin-LR (MC-LR): 96.8%). The addition of SBC filter enhanced the chemical and microbial removal ability of the BAF system. The structure and distribution of biofilm on each filter were different, GAC biofilm accumulated the most MCs degrading microbes, and the highest microbial community richness and diversity was observed in SBC biofilm. Overall, the composite BAF with zeolite-GAC-SBC is developed for algae-laden raw water pretreatment, enabling the application of BAF in drinking water pretreatment plants.